SUCCESSION PLANNING IN SMALL BUSINESS ENTERPRISES IN EDO STATE OF NIGERIA - Obadan, Joseph A.; Ohiorenoya, John O. (European Scientific Journal, ESJ, 2013)
Small business enterprises occupy an important place in any economy. The rate of failure of small business enterprises in the Nigerian economy has been of great concern to all and sundry. One of the reasons for the failure of small business enterprises in Edo State of Nigeria is the lack of succession planning. This study examined the process of succession planning in small business enterprises in the hotel industry in Benin City, Edo State Two hotels were sampled. Questionnaires were used to elicit information from the chief executives and employees. The findings in this study show that most of the small business enterprises have no succession plan in place and the ability and competence of the successors are not considered in succession planning. This study recommends that small business enterprises should develop a formal plan for succession, communicate the identity of successor, provide basic business management education, provide training/monitoring to the incumbent Chief Executive Officer (CEO) and all stakeholders to help him in planning succession and ensuring that owners are comfortable after disengagement.